[OP.LB03.02] NON-INVASIVE HEMODYNAMIC MONITORING IN UNCONTROLLED HYPERTENSIVE PATIENTS: EFFECT ON ARTERIAL STIFFNESS AND CENTRAL BLOOD PRESSURE. (September 2016) - Boutouyrie, P.; Elmula, F.; Rebora, P.; Talvik, A.; Salerno, S.; Miszkowska-Nagorna, E.; Liuc, X.; Comotti, T.; Larstorp, A.; Rostrup, M.; Qwierblewska, E.; Valsecchi, M.; et al.
Abstract : Objective: In the BEAUTY study we investigated whether utilizing non-invasive monitoring of hemodynamic parameters by thoracic impedance plethysmography (IHM) combined with a drug selection algorithm (DSA) compared to conventional drug selection may improve uncontrolled hypertension in European Hypertension Excellence Centres. Although the results of the BEAUTY study on ABPM were neutral (J Hypertens 2015), we investigated whether IHM-DSA could favourably influence central BP and arterial stiffness. Design and method: We selected 183 uncontrolled (office SBP) > 140 mmHg and ambulatory daytime SBP > 135 mmHg while taking > 1 antihypertensive drugs) essential hypertensive patients. If eligible, patients were randomized to IHM-guided (n = 83) vs. conventional (control, n = 84) treatment adjustment in a 6-months, investigator-initiated multicentre prospective randomized parallel groups controlled study. IHM was measured by the Hotman system. Central BP and carotid-femoral pulse wave velocity (CF-PWV) were measured with Sphygmocor. Mixed linear models were used with group, visit and their interaction as factors. Results: As previously published, antihypertensive drug number increased from 3.1 to 4.1 in both groups due to a rise of the use of diuretics in the IHM group (from 13 to 31%). ABPM decreased markedly and similarly in both groups in IHM (−15.8 ± 14.8 mmHg) and in control (−15.4 ± 14.5 mmHg) groups (P = 0.87). Central SBP decreased to the same amount as AMBP and office BP (−13.6 ± 13.5 mmHg, p < 0.0001) and to the same extent in IHM and control groups (mean between group difference −0.22 ± 0.3 mmHg, p = 0.91). Augmentation index did not change with intervention. Carotid to femoral PWV did not change significantly throughout follow-up (−0.20 ± 0.23 m/s, p = 0.80), with no between group difference (p = 0.92). The main determinants of CF-PWV were baseline BP (p < 0.0001) and heart rate (p < 0.001) and changes in BP during follow-up (p = 0.02), however, when accounting for theses variables, CF-PWV tended to increase during follow-up (+0.41, p = 0.20). Conclusions: Thus, despite considerable decrease in brachial BP, though no difference between arms, neither central BP nor aortic stiffness were altered by IHM-DAS compared to conventional drug selection. IHM led to more use of diuretics, known to have inconsistent effects on arterial stiffness and central pressure. This may possibly explain the absence of PWV decrease.